NOBLE GASES IN UREILITES RELEASED BY CRUSHING - Okazaki R.; Nakamura T.; Takaoka N.; Nagao K. (My University, 2003)
Noble gases in two ureilites, Kenna and Allan Hills (ALH) 78019, were measured with two extraction methods: mechanical crushing in a vacuum and heating. Large amounts of noble gases were released by crushing, up to 26.5% of 132Xe from ALH 78019 relative to the bulk concentration. Isotopic ratios of the crush-released Ne of ALH 78019 resemble those of the trapped Ne components determined for some ureilites or terrestrial atmosphere, while the crush-released He and Ne from Kenna are mostly cosmogenic. The crush-released Xe of ALH 78019 and Kenna is similar in isotopic composition to Q gas, which indicates that the crush-released noble gases are indigenous and not caused by contamination from terrestrial atmosphere. In contrast to the similarities in isotopic composition with the bulk samples, light elements in the crush-released noble gases are depleted relative to Xe and distinct from those of each bulk sample. This depletion is prominent especially in the 20Ne/132Xe ratio of ALH 78019 and the 36Ar/132Xe ratio of Kenna. The values of measured 3He/21Ne for the gases released by crushing are significantly higher than those for heating-released gases. This suggests that host phases of the crush-released gases might be carbonaceous because cosmogenic Ne is produced mainly from elements with a mass number larger than Ne. Based on our optical microscopic observation, tabular-foliated graphite is the major carbon mineral in ALH 78019, while Kenna contains abundant polycrystalline graphite aggregates and diamonds along with minor foliated graphite. There are many inclusions at the edge and within the interior of olivine grains that are reduced by carbonaceous material. Gaps can be seen at the boundary between carbonaceous material and silicates. Considering these petrologic and noble gas features, we infer that possible host phases of crush-released noble gases are graphite, inclusions in reduction rims, and gaps between carbonaceous materials and silicates. The elemental ratios of noble gases released by crushing can be explained by fractionation, assuming that the starting noble gas composition is the same as that of amorphous carbon in ALH 78019. The crush-released noble gases are the minor part of trapped noble gases in ureilites but could be an important clue to the thermal history of the ureilite parent body. Further investigation is needed to identify the host phases of the crush-released noble gases.